Self-knowledge in ancient philosophy - Leigh, Fiona (New York : Oxford University Press, 2020)
"In a tradition inspired by the Delphic injunction to 'know thyself', ancient philosophical works contain a variety of treatments of self-knowledge - of knowing the content of certain kinds of one's own thought, or knowing one's own status as a knower or moral agent. This book draws together contributions from an international collection of scholars working in ancient philosophy, and explores self-knowledge in ancient thought in Plato, Aristotle, Hellenistic thinkers, and Plotinus, noting continuities and discontinuities with its contemporary counterpart. The nature and structure of ancient self-knowledge is investigated in different thinkers - whether it is higher-order or a kind of self-presence, consists in a synoptic view or is synchronic, is arrived at directly via self-perception or some other kind of grasp, or mediated by dialogue or friendship with others. So too the book enquires into the relation of self-knowledge to virtue or tranquillity, either as a condition on attaining that state, or a result of the agent's development, resulting from a process of effortful reflection"--